Digitization of Banking Transactions in Algeria: A Structural Lever for Enhancing the Effectiveness of Monetary Policy (Journal of Economic Additions, 2026)
This study analyzes the digitization of Algerian banking as a structural lever to enhance monetary policy effectiveness against the dominance of informal currency circulation. Focusing on the Bank of Algeria (2014-2024), it reveals that digital transformation is vital for reintegrating untracked liquidity, thereby improving decision-making precision and prudential supervision.Crucially, digitization provides a pathway to decouple monetary policy from oil price volatility. The findings advocate for institutional gradualism to maintain stability while paving the way for a sovereign Central Bank Digital Currency  to reinforce national monetary sovereignt.Jel Classification Codes: E52, E58, G21, O33, E42.
Keywords: Monetary policy, digitalization of banking transactions, informal economy, off-banking transactions, financial stability.